Improving Educational Outcomes through Getting It Right for Every Child in Glasgow. (15th August 2020) - McKenna, Maureen
Abstract : This article sketches the context of education in Glasgow, which is Scotland's largest local authority, serving some of the most deprived communities in Scotland and the UK. It considers the ways in which we work with our schools to raise aspirations and extend young people's horizons, and explores some of the successes and some of the challenges we have faced and continue to face in bridging the gap between school and higher education. In Scotland, higher education can be delivered through colleges as well as universities. This is an important dimension for our young people, as colleges offer a different learning experience for them and, for some, this can be a more successful learning pathway. There are also other pathways to higher education, for example through work-based learning, such as apprenticeships. Our partnerships with universities and colleges is very strong. Through this partnership there is a range of programmes which support young people across the city to learn about life in university. This is especially important for young people from deprived communities as, often, their families do not have prior experience of higher education. The means of funding and planning these programmes can be viewed as both an enabler and a barrier in certain contexts.